Ruth Schneider: diálogos entre a artista e sua obra (décadas de 1980 e 1990) - Carmo, Aline do (2021)
Brazilian artist Ruth Schneider (1943–2003) began painting in the late 1970s. Her life trajectory is marked by the theme of art, as she had a vigorous artistic production. These works were produced until 2003, when he died, in Porto Alegre/RS. The objective of the thesis is to investigate the narratives present in the artist's life and work that bring together personal and historical facts in visual works. Therefore, instead of working with movements and dates, in this thesis, I present an autofictional vision of Ruth Schneider, designer, painter and sculptor, building it based on themes such as “biased narratives”, time and memory, the art and space.The hypothesis of this thesis is that these times in Schneider's work are many: a time is mine, a researcher in front of works, documents, videos; the other is that of the painter herself and her artistic production, the technique she used, her plastic and aesthetic references; another time is Ruth's memory and my own memories.With the crossing of these temporalities, the artist's mental tools were sought, at the time of the work's production, so that they could be a source of understanding of what made that representation possible.I intend to extend the analysis of Ruth Schneider, a painter from Passo Fundo, who started with the dissertation “Art and history in the Cassino da Maroca series by Ruth Schneider”, introducing a change of focus in the debate, using the autobiographical audiovisual archives that gave another perspective to the research: the history of the works told by the artist herself.The artist's construction process is permeated by tactics that were woven throughout her life, in the concrete experience of art. crossing these temporalities, the artist's mental tools were sought, at the time of the work's production, so that they could be a source of understanding of what made that representation possible. I intend to extend the analysis of Ruth Schneider, a painter from Passo Fundo, who started with the dissertation “Art and history in the Cassino da Maroca series by Ruth Schneider”, introducing a change of focus in the debate, using the autobiographical audiovisual archives that gave another perspective to the research: the history of the works told by the artist herself.The artist's construction process is permeated by tactics that were woven throughout her life, in the concrete experience of art. The sources used for the research are, centrally, audiovisual archives (74 VHS videos from the artist's private collection), although written sources, interviews and iconographic materials such as: paintings, sculptures, artistic installations, personal diaries, newspapers and advertising materials. By analyzing her ideas, it was possible to see how she was able to elaborate plastic works that justify her way of existing, as well as her history.To this end, the method of history of self-fiction was used, which is “fiction of strictly real events and facts”, according to Doubrovsky (1977), which launched the term in the French market. Vicente Colonna created a typology of self-fiction, using biographical self-fiction as a type, in which subjectivity replaces sincerity – thanks to the “truelying” mechanism. An incessant artist, he literally talked with his works, leaving a record of this spontaneous experimentalism in annotations and audiovisual recordings. Cut, painted, glued, drilled and crushed its supports. He drew with his hands, generating unexpected gestures that exploded in strong colors. Always researching the processes of form, he used unusual materials that established quite unique relationships among themselves and created an expressive amount of works that declare the bankruptcy of the hierarchy between painting, drawing, sculpture or installation.